Reading and Writing Verse in Medieval to Early Modern Iceland - Ásdís Hermanowicz 1983- (2017)
This study provides both a synchronic analysis of scribal approaches to layout and punctuation of Latin and vernacular verse in medieval Icelandic manuscripts and a diachronic overview of changing conventions of writing vernacular verse into the early modern period. Fundamental to this thesis is the argument that the visual presentation of a text provides important information about the significance and use of the literary work within the culture that produced it. Latin writing conventions created the basic conditions and possibility for writing in the vernacular. Yet medieval scribes inconsistently adopted the conventions used in Latin writing specifically for verse. This thesis provides examples of the conventions set by Latin verse and the instances in which scribes followed or ignored these conventions when writing verse in the vernacular. The differences in the visual presentation of medieval vernacular and Latin verse indicate that these two metrical systems were perceived as different categories of speech and writing. Ultimately, this thesis argues that it is significant for the history of reading and the development of genres of poetry in Iceland that during the seventeenth century, poetic texts began to be presented using spatial forms such as lineation to indicate structure. The shift toward the spatial layout of vernacular poetry and—in the case of the stanzas embedded in saga prose—the visual distinction of poetry from prose is tied to a shift in the regard for poetry as a primarily textual entity through which the poet has a direct connection to the reader. Í þessari ritgerð er kannað hvernig samtíma skrifarar íslenskra handrita á miðöldum settu fram og greinarmerkjasettu latneskan og íslenskan kveðskap. Um leið er kannað hvernig hefðin á að skrifa íslenskan kveðskap breyttist allt fram til nútímans. Grundvallarhugmynd þessarar ritgerðar er sú að sjónræn framsetning texta gefi merkilegar upplýsingar um mikilvægi og notkun textans innan þeirrar menningar sem hann gat. Latneskar skrifhefðir sköpuðu ...